Penyelesaian Sengketa Pembagian Warisan Antar Ahli Waris: Perspektif Hukum Perdata (Studi Kasus Pengadilan Negeri Sragen) - SUPRIYANI, WIWIN, Septarina, S.H., M,H, Nuswardani, S.H, S.U (2015)
This study aims to determine how the position and rights of each heir in the division of inheritance, describing the consideration of evidence and the judge in determining the verdict on the case inheritance among heirs. The method used is a normative juridical approach through a descriptive approach. Types and sources of data comprising primary and secondary data. Data were collected through library research and interview, then analyzed by qualitative analysis method. The results showed the position of heir is the biological child, so the heir to inherit a position and have the right to get the same parts. Consideration of the judge in determining the evidentiary case, caused the defendant can not prove the ownership of land belonging to his father's yard, so the rebuttal given by the defendant was not proven. Consideration of the judge in determining the verdict in inheritance disputes between the Plaintiffs and the Defendants granted partly and refusing to apart and rest, because the plaintiff is the biological child of the testator and the Defendants was the granddaughter of the testator.